Modified Double-Eyelid Blepharoplasty Using the Single-Knot Continuous Buried Non-Incisional Technique - Kyung-Chul Moon (Archives of Plastic Surgery, 2013)
BackgroundBuried non-incisional double-eyelid blepharoplasty is a popular aesthetic procedure. Although various modified continuous suture techniques have been used to create a more natural appearance and to reduce downtime, complications such as loosening of the double fold, asymmetry, and foreign body reactions have been observed.MethodsThis study included 250 patients who underwent double-eyelid blepharoplasty between March 1997 and November 2012 using a modified single-knot continuous buried non-incisional technique. With 4 stab incisions in the upper eyelids, one of two needles loaded with double-armed 7-0 nylon was passed in one direction alternately through the dermis and the conjunctiva, while the other needle was passed subconjunctivally in the opposite direction. Both ends of the sutures were knotted within a lateral stab incision of the upper eyelids and were buried in the orbicularis oculi muscle.ResultsMost patients displayed satisfactory aesthetic results, and no significant complications occurred. There was no obvious regression of the double fold; however, 3 patients required reoperation to correct loosening of the fold on one side during the follow-up period. One patient presented with the suture knot subcutaneously, and the knot was removed in the clinic.ConclusionsThe modified single-knot continuous buried non-incisional technique is a simple and less time-consuming method for a durable double fold and provides satisfactory aesthetic results.